2014
DOI: 10.1002/oby.20731
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of social networks and child obesity prevention program effects: The pathways trial

Abstract: Objective Social network analysis was used to examine whether peer influence from one’s social networks moderates obesity prevention program effects on obesity related behaviors: healthful behaviors and unhealthful ones. Design and Methods Participants included 557 children residing in Southern California. Survey assessed health promoting behaviors (i.e., physical activity at school, physical activity outside of school, and fruit and vegetable intake), as well as unhealthful ones (high calorie low nutrient i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 34 publications
3
33
0
Order By: Relevance
“…While social support from parents, siblings, and peers has been extensively studied as a predictor of physical activity participation [1820] and dietary behavior change [21, 22], our findings lend support to mounting evidence that children’s family and social networks can be leveraged to cultivate and reinforce improvements in weight status [23, 24]. The social learning theory stresses that individuals learn their behavior and new skills from observing others, termed modeling [25].…”
Section: Discussionsupporting
confidence: 68%
“…While social support from parents, siblings, and peers has been extensively studied as a predictor of physical activity participation [1820] and dietary behavior change [21, 22], our findings lend support to mounting evidence that children’s family and social networks can be leveraged to cultivate and reinforce improvements in weight status [23, 24]. The social learning theory stresses that individuals learn their behavior and new skills from observing others, termed modeling [25].…”
Section: Discussionsupporting
confidence: 68%
“…These social norms are not always salutogenic but can be targets for intervention. For example, a school-based study of 5 th -graders gathered information on peer connectedness and exposure to friends’ healthful and unhealthful PA and diet behaviors [41]. The behaviors of students who were randomized to participate in an obesity-prevention program did not appear to be influenced by friends with unhealthy behaviors.…”
Section: Current State Of the Field: What We Knowmentioning
confidence: 99%
“…Those studies that do examine change in social network structure in group interventions suggest that significant interaction effects exist and that more research in this area is needed to fully understand how to leverage network effects to accelerate complex health behavior change (Gesell, Bess, & Barkin, 2012; Shin et al, 2014; Valente et al, 2007). This study reveals that new, and potentially strong, social ties can develop within the first months of a group level health intervention; the ties that developed extended beyond the intervention context, and the type of communication ties that developed indicated that trust was developing between intervention participants.…”
Section: Discussionmentioning
confidence: 99%